Adapting to climate change on desert rangelands: A multi-site comparison of grazing behavior plasticity of heritage and improved beef cattle. (February 2023) - Cibils, Andres F.; Estell, Rick E.; Spiegal, Sheri; Nyamuryekung'e, Shelemia; McIntosh, Matthew M.; Duni, Danielle M.; Herrera Conegliano, Oscar A.; Rodriguez Almeida, Felipe A.; Roacho Estrada, Octavio; Blanco, Lisandro J.; Duniway, Michael C.; Utsumi, Santiago A.; et al.
Abstract: Climate change is amplifying the spatiotemporal heterogeneity of desert rangeland forages through its impact on precipitation variability. Foraging behavior plasticity (an animal's ability to alter its behavior to cope with environmental variation) could be a key trait for climate adaptation of beef cattle in arid environments. We analyzed GPS-derived movement and activity data of Criollo and commercial beef cattle from eight studies conducted at sites in North and South America to determine whether seasonal and year-to-year behavior plasticity varied significantly between breeds. We calculated dormant/brown season or driest year percent change in foraging behavior relative to growing/green season or wettest year. Compared to commercial beef breeds, Criollo cattle exhibited significantly greater seasonal adjustment in daily distance traveled (20% increase vs. 2% decrease, P ≤ 0.02) and daily grazing effort (25% vs. 1.5% increase, P = 0.01) during the dormant/brown vs. growing/green season. Increase in daily area explored during the dormant/brown season was almost three times greater in Criollo vs. commercial beef cattle (P = 0.09). Seasonal adjustment in daily time spent grazing was similar for Criollo and commercial beef breeds. Increase in daily area explored during the dormant/brown season of dry vs. wet years was three times greater for Criollo vs. commercial beef breeds (P = 0.03). Criollo cattle tended (P = 0.09) to exhibit greater behavior adjustment than commercial beef counterparts in daily distance traveled during the dormant/brown season of dry vs. wet years (22% vs. 4% increase, respectively). No breed differences in adjustment of time spent grazing (P = 0.36) or grazing effort (P = 0.20) during dormant/brown season of dry vs. wet years were observed. Dry vs. wet year grazing behavior adjustments during the growing/green season were similar for both breeds. Grazing behavior plasticity observed in Criollo cows could be a critical trait for desert beef herds in the face of increasingly variable rainfall patterns occurring as a result of climate change.